Optimizing Preventive Maintenance Strategy at The Ottawa Hospital through the Application of Alternative Equipment Maintenance - Sangargir, Maryam; Brose, Joel (CMBES Proceedings, 2024)
<div class="min-h-[20px] text-message flex flex-col items-start gap-3 whitespace-pre-wrap break-words [.text-message+&]:mt-5 overflow-x-auto" data-message-author-role="assistant" data-message-id="d1cf868c-ba7c-4fbf-be87-0be17f18d16c"> With the goal of improving Preventive Maintenance (PM) practices, The Ottawa Hospital (TOH) has launched the Alternative Equipment Management (AEM) project. AEM introduces a systematic approach for scenarios where there is a need to deviate from manufacturer-recommended maintenance recommendations, aligning practices with the hospital’s specific needs. This evaluation focuses on safety prioritization, the integration of World Health Organization (WHO) guidelines, and establishing a dedicated AEM committee. <button class="flex items-center gap-1.5 rounded-md p-1 text-xs hover:text-gray-950 dark:text-gray-400 dark:hover:text-gray-200 disabled:dark:hover:text-gray-400 md:invisible md:group-hover:visible md:group-[.final-completion]:visible">